Die deutsche Fischerei auf Blauleng im Nordost-Atlantik 1984 - Reinsch, H.H. (1985)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010